Morphological descriptions of second and third instar larvae of hypopygiopsis violacea Macquart (Diptera: Calliphoridae), a forensically important fly in Malaysia - Firdaus, A.M.S.; Marwi, M.A.; Syamsa, R.A.; Zuha, R.M.; Ikhwan, Z.; Omar, B. (2010)
Hypopygiopsis violacea, a species of fly of forensic importance, was recovered from a corpse and described for the first time. The morphological structures of the second and third instar larvae of four specimens were examined using light microscope. Observations were focused on three main morphological characters: cephalopharyngeal skeleton, anterior and posterior spiracles. Cephalopharyngeal skeleton of second instar larva is darkly pigmented and without accessory sclerite below the mouth hook. The anterior spiracles of second and third instar larvae have 8-9 papillae each, arranged in a single row. The posterior spiracles of second instar larva has two spiracular slits with no thickening of peritreme. This differentiates it from the third instar, whereby the latter has three slits for each posterior spiracle. Cephalopharyngeal skeleton of third instar larva is heavily pigmented. An accessory sclerite is found below the hook part of third instar larva but is absent in second instar. Peritreme of the posterior spiracle of third instar larva is thick almost complete encircling a button. The intersegmental spines of the cuticular surface are dome-shaped and unicuspid. Third instar larva of this species is large with size approximately 15 mm long. These findings provide important identification features of immature stages of Hy. violacea which could be useful in forensic entomology.